Quality of Life of Patients with Type II Diabetes Mellitus in Al- Hilla City-Iraq - Haydar F. Al - Tukmagi; Miamin A. Moussa (College of Pharmacy University of Baghdad, 2017)
Diabetes mellitus is a global problem nowadays due to increase the disease cases all over the world, in both the developed and developing countries which may affect the quality of life (QOL ) of diabetic patients. This study was conducted to assess the quality of life of patients with type 2 diabetes mellitus (DM) and to determine some selected clinical and sociodemographic factors that affect the quality of life of these patients in Al Hila city-Iraq. This was a cross sectional study in which 100 patients with type 2 diabetes mellitus attending diabetic outpatient clinics of Merjan Teaching Hospital-Al Hila. To assess the quality of life of those diabetic patients, the World Health Organizations Quality of Life Assessment (WHOQOL) was applied, but in a short version questionnaire and abbreviated form called (WHOQOL-BREF). Concerning the results of this study, it was found that the patients responded fairly well on the questionnaire used, 39% had good score, 47% had fair score and 14% had poor score. For physical health domain 17% had poor score, for social domain 22% had poor score, for psychological domain 19% and environmental domain 18% had poor score. It was concluded from the results that although it supports previous reports in which QOL of patients with DM were fairly good but this disease is significantly affects physical health, social relations and environment. Furthermore, there is association with marked impairment in aspects of quality of life relating to mental health and psycho-social functioning and at least some aspects of physical health. Given this, and given its high prevalence, greater attention is needed to watch DM as a public health problem. The fact that DM is â€œnormativeâ€ should not be taken to infer that it is benign. Keywords: Diabetes mellitus, Quality of life.